2016
DOI: 10.1371/journal.pone.0156063
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of the Tyrosine Kinase Syk in Regulation of Toll-Like Receptor Signaling in Plasmacytoid Dendritic Cells

Abstract: Crosslinking of regulatory immunoreceptors (RR), such as BDCA-2 (CD303) or ILT7 (CD85g), of plasmacytoid dendritic cells (pDCs) efficiently suppresses production of type-I interferon (IFN)-α/β and other cytokines in response to Toll-like receptor (TLR) 7/9 ligands. This cytokine-inhibitory pathway is mediated by spleen tyrosine kinase (Syk) associated with the ITAM-containing adapter of RR. Here we demonstrate by pharmacological targeting of Syk that in addition to the negative regulation of TLR7/9 signaling v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
(51 reference statements)
3
22
0
Order By: Relevance
“…This data is consistent with previous reports demonstrating that Syk kinase is essential for mediating NK cell killing function [31]. While a majority of the TLR signaling pathways are mediated by IRAK4 kinase [32], we observed that inhibitors of other kinases such as PI3Kδ, SYK/ZAP-70 and JAK also have an impact on functional TLR responses, consistent with previous reports [3335]. Among the TLR responses evaluated, cyclosporine, PI3Kδ and SYK/ZAP70 inhibitors inhibited TLR3 and TLR9, but not TLR7 induced responses.…”
Section: Discussionsupporting
confidence: 93%
“…This data is consistent with previous reports demonstrating that Syk kinase is essential for mediating NK cell killing function [31]. While a majority of the TLR signaling pathways are mediated by IRAK4 kinase [32], we observed that inhibitors of other kinases such as PI3Kδ, SYK/ZAP-70 and JAK also have an impact on functional TLR responses, consistent with previous reports [3335]. Among the TLR responses evaluated, cyclosporine, PI3Kδ and SYK/ZAP70 inhibitors inhibited TLR3 and TLR9, but not TLR7 induced responses.…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed that GS‐9973 (1.0 μM) effectively inhibited SYK phosphorylation at Y525/526 (Fig. B), the key activation site at the kinase domain of SYK . We also found that GS‐9973 down‐regulated protein expression of α‐SMA, PDGFRβ and PAI‐1 (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Another report suggested a role for the C330b-DAP12-TLR4-Syk-PI3K signaling complex in amplifying inflammatory responses in macrophages (53). A role for Syk in the regulation of TLR signaling in pDCs is also observed (54). These studies and our results show that the FcγRIIIa-pSyk signaling induced NA-TLRs are critical for CD4 + T-cell responses.…”
Section: Discussionmentioning
confidence: 97%